B7‐H4 deficiency in salivary gland of patients with primary Sjögren's syndrome impairs the regulatory effect on T cells. (20th February 2017) - Li, Xiaomei; Yu, Daliang; Yu, Ning; Wang, Ximei; Li, Xiangpei; Harris, David C. H.; Wang, Yiping
Abstract: Aim: Our previous study confirmed the defect of B7‐H4 expression in peripheral blood and salivary glands of patients with primary Sjögren's syndrome (pSS). The aim of this study was to analyze the effect of the deficit expression of B7‐H4 on CD4 + T cells. Methods: CD4 + T cells were purified by magnetic‐activated cell sorting MACS. The proliferation and cytokine production of CD4 + T cells co‐cultured with purified salivary gland epithelial cells (SGECs) from pSS or non‐SS sicca syndrome were detected. Results: By co‐culturing the gland cells with CD4 + T cells, we found the proliferation of CD4 + T cells was significantly suppressed. The effect was weaker when SGECs from pSS patients were used compared to that from non‐pSS sicca syndrome controls. Simultaneously, the productions of cytokines interleukin (IL)‐5, IL‐13, IL‐17A, IL‐6 in supernatant were reduced and also SGECs from pSS patients decreased them less than that from non‐SS controls. Conclusions: The decrease of B7‐H4 expression in salivary glands of SS patients contributes to the defect of negatively regulating the inflammation caused by CD4 + T cells, thereby providing new insights into the role of B7‐H4 in the inflammatory process of salivary glands in SS.